2017
DOI: 10.17338/trainology.6.1_26
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a duration standard for the calculation of session rating of perceived exertion in NCAA division I men’s soccer

Abstract: Objectives:The purpose of this study was to determine the best predictor of training and/or match load using session RPE. Design and Methods: 20 NCAA DI male soccer players participated in the study during the 2014 and 2015 competitive seasons.Players completed 15.20 ± 1.05 matches for a total of 304 individual data points and 29.90 ± 1.89. training sessions for a total of 598 individual data points. GPS variables (total distance, High-intensity running distance, and Player load) were analyzed with session RPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…An important practical consideration when using sRPE-TL is how the duration is being quantified, specifically during match play. Pustina et al [ 34 ] reported differences in sRPE-TL measures based on how the session duration was defined (i.e., including or excluding warm-ups and half-time, only including on-field playing time, etc.) and found that sRPE-TL calculated using only on-field playing time was the best reflection of external workloads incurred during the match play.…”
Section: Discussionmentioning
confidence: 99%
“…An important practical consideration when using sRPE-TL is how the duration is being quantified, specifically during match play. Pustina et al [ 34 ] reported differences in sRPE-TL measures based on how the session duration was defined (i.e., including or excluding warm-ups and half-time, only including on-field playing time, etc.) and found that sRPE-TL calculated using only on-field playing time was the best reflection of external workloads incurred during the match play.…”
Section: Discussionmentioning
confidence: 99%
“…The mean difference in discarded versus retained data was trivial (r = 0.06, range = 0.01 to 0.23). We further identified five studies [22,23,26,27,35] meeting our inclusion criteria in which duplicate data were evident. To avoid the issue of double counting in our meta-analyses [47], we made informed decisions to discard these data.…”
Section: Selection Of Datasets and Estimatesmentioning
confidence: 99%
“…To avoid the issue of double counting in our meta-analyses [47], we made informed decisions to discard these data. One study [27] reported the relationships between sRPE training load (sRPE-TL) and three external load indicators using different measures of session volume in the calculation of sRPE-TL (i.e. total match duration, minutes played, and the addition of halftime and warm-up periods).…”
Section: Selection Of Datasets and Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…As this is the first study to assess internal load during a school soccer competition with a 24 h interval between games, the results found cannot be compared to other studies. Although session-RPE has been widely accepted as a valid parameter for assessing the physiological stress of a training session or competition 4,25,26 , there are few studies that have evaluated this variable in a game situation 25,26 . Previous studies have shown that exercise intensity affects this variable 27,28 , which suggests that the effort intensity of players in the fourth game was higher than in other games.…”
Section: Discussionmentioning
confidence: 99%